Procedures to Reduce Haemorrhage during Myomectomy for Fibroids - Winata, I Gede Sastra; Lazarosony, Nicholas Renata (PT Kalbe Farma Tbk., 2022)
Uterine fibroids are the most common solid tumors in the female pelvis. Myomectomy is the first choice of treatment for woman who want to keep their uterus. Haemorrhage, uterine perforation, cervical injury, and metabolic problems from excessive absorption of the distension medium, such as glycine, are risks of hysteroscopic myomectomy. There are several procedures and techniques to reduce haemorrhage during myomectomy for fibroids. Some research demonstrated excellent outcomes with uterine artery ligation. Mioma uteri adalah tumor jinak yang paling sering dijumpai pada wanita. Tindakan miomektomi adalah salah satu pilihan terapi padawanita yang tetap ingin mempertahankan rahim. Perdarahan, perforasi uterus, cedera serviks, dan masalah metabolisme akibat penyerapan berlebihan media distensi, seperti glisin, adalah risiko prosedur histeroskopi miomektomi. Beberapa prosedur dan teknik dapat mengurangi perdarahan saat miomektomi pada kasus mioma uteri. Beberapa penelitian menunjukkan hasil yang sangat baik dengan ligasi arteri uterina.